Superwoman si inay! Mommy is superwoman! - Matias, Segundo D.; Bravo, Becky; Garcia, Edith (Maynila Lampara Publishing House, Inc., 2010)
"As a mother, mommy Doris has a quality that makes her capable of providing anything her children need. read in this story why mommy Doris is really awesome."
"Stories with moral values."
Text in English and Filipino.
Keywords: Children's stories, Philippine (English)